Sistem Monitor Suhu dan Kelembaban Berbasis Cloud pada Lahan Gambut - Satrio Yudho Prakoso; Ade Agung Harnawan; Muhammad Itqan Mazdadi; Yoga Pambudi (Jurnal Fisika Flux: Jurnal Ilmiah Fisika FMIPA Universitas Lambung Mangkurat, 2022)
The Research and Development Center for The Soil and Agricultural Land Resources Office estimates that Indonesia's peatland area is around 14.9 million H. In the dry season, peatlands experience dryness, so they burn easily. More than 99% of the causes of forest and peatland fires are human-made, either deliberately burning or neglecting to use fire. IoT (Internet of Things) technology is used to connect all devices to the internet and enable communication of each other, one reason for which is that digital data stored on cloud storage, then display the data on a website. The website was designed to monitor the peat's condition by considering the peat's air temperature, peat soil temperature, peat soil moisture, and humidity around the peatlands. IoT retrieves and sends data to the cloud, then websites retrieve and display data from the cloud in diagram and table format for easy reading of monitors. Website monitoring systems utilize several components, including domains as addresses, web hosting as web data storage, and the CMS framework CodeIgniter is used as the basis of the application. Sending data from IoT to web hosting requires cloud storage. Without this, it is necessary to transfer data from the IoT to the website manually. The monitor system can read temperature and humidity sensor data, store it in the cloud, then display it on a website so that the data monitoring process runs well.